2006
DOI: 10.3201/eid1211.060671
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices of Avian Influenza, Poultry Workers, Italy

Abstract: We asked Italian poultry workers about knowledge, attitudes, and practices regarding avian influenza. It was perceived to be a low occupational hazard, and wearing protective equipment and handwashing were not routine practices. Knowledge of transmission and preventive measures should be improved. Employers and health professionals should provide more effective information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
81
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(105 citation statements)
references
References 3 publications
16
81
5
Order By: Relevance
“…Knowledge about biosecurity and risk factors varied widely between urban/periurban (51 correct answers) and rural (25 cor- Our fi ndings are similar to trends reported among poultry workers in previous studies (3,4) (Table). Our study showed that knowledge of food safety and risk factors and differentiation between HPAI and other poultry diseases is poor among the poultry farming communities of Nigeria.…”
supporting
confidence: 81%
“…Knowledge about biosecurity and risk factors varied widely between urban/periurban (51 correct answers) and rural (25 cor- Our fi ndings are similar to trends reported among poultry workers in previous studies (3,4) (Table). Our study showed that knowledge of food safety and risk factors and differentiation between HPAI and other poultry diseases is poor among the poultry farming communities of Nigeria.…”
supporting
confidence: 81%
“…These results support previous fi ndings that knowledge about avian infl uenza, especially about prevention and human-to-human transmission, has scope for improvement (4,5). Persons in Europe reported that they have little ability to prevent themselves from getting avian infl uenza (6).…”
Section: Knowledge About Avian Infl Uenza European Regionsupporting
confidence: 81%
“…Several reports have examined KAPs and behavior related to avian infl uenza (H5N1) (6)(7)(8)(9). Similar to the fi nding in the Lao People's Democratic Republic (6), our study suggests that conventional education and behavior change messages have a limited effect in populations with highest exposure.…”
Section: Discussionmentioning
confidence: 99%